Nanoparticle-Based Drug Delivery Systems Targeting Tumor Microenvironment for Cancer Immunotherapy Resistance: Current Advances and Applications - Peijie Wu; Jun Han; Yanju Gong; Chao Liu; Han Yu; Na Xie (MDPI AG, 2022)
Cancer immunotherapy has shown impressive anti-tumor activity in patients with advanced and early-stage malignant tumors, thus improving long-term survival. However, current cancer immunotherapy is limited by barriers such as low tumor specificity, poor response rate, and systemic toxicities, which result in the development of primary, adaptive, or acquired resistance. Immunotherapy resistance has complex mechanisms that depend on the interaction between tumor cells and the tumor microenvironment (TME). Therefore, targeting TME has recently received attention as a feasibility strategy for re-sensitizing resistant neoplastic niches to existing cancer immunotherapy. With the development of nanotechnology, nanoplatforms possess outstanding features, including high loading capacity, tunable porosity, and specific targeting to the desired locus. Therefore, nanoplatforms can significantly improve the effectiveness of immunotherapy while reducing its toxic and side effects on non-target cells that receive intense attention in cancer immunotherapy. This review explores the mechanisms of tumor microenvironment reprogramming in immunotherapy resistance, including TAMs, CAFs, vasculature, and hypoxia. We also examined whether the application of nano-drugs combined with current regimens is improving immunotherapy clinical outcomes in solid tumors.